The binding of cholera toxin to the periplasmic vestibule of the type II secretion channel - Reichow, Steve L (Landes Bioscience, 2011)
The type II secretion system (T2SS) is a large macromolecular complex spanning the inner and outer membranes of many Gram-negative bacteria. The T2SS is responsible for the secretion of virulence factors such as cholera toxin (CT) and heat-labile enterotoxin (LT) from Vibrio cholerae and enterotoxigenic Escherichia coli, respectively. CT and LT are closely related AB(5) heterohexamers, composed of one A subunit and a B-pentamer. Both CT and LT are translocated, as folded protein complexes, from the periplasm across the outer membrane through the type II secretion channel, the secretin GspD. We recently published the 19 Å structure of the V. cholerae secretin (VcGspD) in its closed state and showed by SPR measurements that the periplasmic domain of GspD interacts with the B-pentamer complex. Here we extend these studies by characterizing the binding of the cholera toxin B-pentamer to VcGspD using electron microscopy of negatively stained preparations. Our studies indicate that the pentamer is captured within the large periplasmic vestibule of VcGspD. These new results agree well with our previously published studies and are in accord with a piston-driven type II secretion mechanism.